Enzyme alkaline phosphatase (ALP) and acid phosphatase (ACP) levels in Gir cattle and Jaffarabadi buffaloes - PADODARA, R.J.and GAJBHIYE, P.U., NINAN JACOB1, ARYA, J.S (Indian Journal of Animal Production and Management, 2020)
Plasma Alkaline Phosphatase (ALP) and Acid Phosphatase (ACP) levels were determined using standarddiagnostic kits in male and female Gir cattle and Jaffarabadi buffalo at different ages (1 wk to 36 months),lactation months (1m to 3m), non-lactating animals (pregnant and non-pregnant) and in bulls and castratedmales. Significant (P < 0.05) effect of age was seen in all four groups studied for plasma alkaline phosphataseand acid phosphatase (except in Jaffarabadi males) activities. The activity differed significantly (P < 0.05)between different lactation months in Gir cows and Jaffarabadi buffaloes for ALP. The significant (P < 0.05)effect of lactation was seen only in Gir cows with respect to ACP activity. Significant (P < 0.05) differenceswere observed between non-lactating stages for ALP (in Gir cows) and ACP (in Jaffarabadi buffaloes)activities. The levels of ALP and ACP differed significantly (P < 0.05) between Gir bulls and castratedanimals. The enzyme activities between the females and between the males of Gir and Jaffarabadi speciesvaried significantly (P < 0.05) for both the enzymes studied. The effect of lactation between Gir cows andJaffarabadi buffaloes was found significant (P < 0.05) at different months of lactation for both the enzymes.The activities between Gir and Jaffarabadi in the non-lactating group differed significantly for ACP (bothpregnant and non-pregnant), and for ALP (in pregnant). The values between bulls of Gir and Jaffarabadidiffered significantly (P < 0.05) for ALP and ACP activities.